Carbon monoxide poisoning: assessment, treatment, and outcomes - Zein, Ahmed Ragab; Almalki, Eidan Bakheet; Almasabi, Hani Ahmed; Alzahrani, Hatem Tarig; Alabdali, Rehab Hassan; Alsalamah, Zainab Kadim; Alhaeti, Haitham Rasheed; Alsuroji, Abdullah Hadi; Bugis, Ashwaq Hussain; Sadiq, Fatima Abdullah Al; Almohammadi, Muath Yousef (International Journal Of Community Medicine And Public Health, 2021)
Many complications can occur secondary to carbon monoxide (CO), including serious complications to the cardiovascular system and neurological complications that might even end up with death. It has been estimated that around 30-40% of patients suffering from CO poisoning usually die before presenting at the emergency department. Accordingly, management of these patients is a critical approach to enhance the outcomes and prognosis of the affected patients. In the present literature review, we have discussed the current evidence regarding the assessment, treatment, and outcomes of patients with CO poisoning. Our results indicate that attending clinicians should adequately assess the suspected patients with their clinical manifestations, laboratory parameters, and history of exposure to CO. Besides, imaging techniques can also be indicated in some cases with a suspected brain injury. After the diagnosis has been successfully established, management of symptoms and administration of the validated therapeutic modalities should be rapidly performed to enhance the outcomes and intervene against the development of further complications. However, it should be noted that even after achieving adequate management, long-term complications might develop with the survivors and can even lead to death. Accordingly, further research is needed to help formulate successful interventions that can enhance the prognosis of the condition.